An Analysis of Sustainable Land Management Strategies for Controlling Soil Degradation in Tropical Agricultural Areas - Ruth Riah Ate Tarigan (Jurnal Multidisiplin Sahombu, 2026)
Soil degradation remains a critical challenge in tropical agricultural areas due to intensive land use, unsustainable farming practices, deforestation, and climate variability, which collectively threaten agricultural productivity and environmental sustainability. This study aims to analyze sustainable land management (SLM) strategies in controlling soil degradation in tropical agricultural areas. The research employs a descriptive-analytical approach based on secondary data obtained from scientific publications, government reports, and international databases, complemented by a comparative analysis of various land management practices applied in tropical regions. The analysis focuses on key SLM strategies, including soil conservation techniques, agroforestry systems, integrated nutrient management, land-use planning, and community-based land management. The results indicate that the implementation of sustainable land management practices significantly contributes to reducing soil erosion, improving soil fertility, and enhancing land productivity while maintaining ecological balance. Agroforestry and conservation agriculture are identified as the most effective strategies due to their ability to integrate economic, environmental, and social benefits. However, the effectiveness of these strategies is strongly influenced by institutional support, farmer awareness, policy consistency, and local socio-economic conditions. This study highlights the importance of integrated and adaptive land management policies to mitigate soil degradation and promote long-term agricultural sustainability in tropical regions. The findings are expected to provide valuable insights for policymakers, practitioners, and researchers in developing effective land management frameworks to support sustainable agricultural development.